Investigation of disequilibrium clumped isotope fractionation in (speleothem) CaCO3 with cave analogous laboratory experiments using thin films of flowing solution - Hansen, Maximilian; Kluge, Tobias; Scholz, Denis (Geochimica et cosmochimica acta, 2022)
Here we present clumped isotope Δ47 data of cave analogous experiments. We investigate the evolution of the Δ47 values of both the dissolved inorganic carbon (DIC) and the CaCO3 of thin-films flowing down in channels along inclined marble and glass plates precipitating CaCO3 along the flow path. With increasing distance of flow and residence time on the plate, we observe large deviations from the initial Δ47 values, along with increasingly over-estimated apparent Δ47- temperatures derived from the precipitated CaCO3. With further increasing residence time on the plates (>250 s) and decreasing supersaturation with respect to calcite, the CaCO3 Δ47 values start to approach the initial equilibrium values again. This highlights the potentially strong effect of disequilibrium isotope effects on clumped isotope temperatures derived from speleothems, in particular because the disequilibrium effect on the Δ47 values is most pronounced in the first few 100 seconds of CaCO3 precipitation. The experimental Δ47 values are consistent with a recent modeling study by Guo and Zhou (2019). The maximum degree of disequilibrium, however, seems to be more pronounced than predicted by the model for some of the experiments. A potential reason for this observation is that suitable kinetic fractionation factors are so far not available. While the Δ47 values of the CaCO3 decrease along the plate as the model suggests for the Δ47 values of the HCO3−, those of the DIC increase and follow the modelled Δ47 values of the dissolved CO2. Based on our study, we can neither confirm nor exclude a temperature dependence of the Δ47-δ18O slope as well as a dependence on cave pCO2, which highlights the complexity of this relationship. In addition, the non-linear evolution of Δ47 and δ18O values with time and along the flow path restricts a correction of the Δ47 and δ18O values based on the Δ47-δ18O slope to the initial phase of the isotope evolution. So far, a correction of the kinetic isotope effects is not yet possible, but this might be important in future studies if the disequilibrium slope on a Δ47-δ18O diagram could be precisely determined for the initial phase of isotope evolution.
Im Text ist "3" tiefgestellt
Available online 23 December 2021
Gesehen am 23.05.2022